Analisis Peran Jumlah Wisatawan dan Jumlah Kamar Hotel terhadap PDRB Per Kapita Kabupaten Musi Banyuasin - Nazhirah, Afra; Syaputra, Kamilia; Novrianty, Rizky (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
Tourism is a strategic sector in regional development because it can provide a multiplier effect on economic activity, including contributing to Gross Regional Domestic Product (GRDP). However, the extent to which tourism indicators such as the number of tourists and accommodation capacity influence regional economic growth still shows varying results across regions. This study aims to analyze the influence of the number of tourist visits and the number of hotel rooms on GRDP per capita in Musi Banyuasin Regency during the 2019–2024 period. The research method uses a quantitative approach with multiple linear regression analysis based on secondary data obtained from the Central Statistics Agency. The results show that both variables have no significant effect either simultaneously or partially. The coefficient of determination (R²) value of 0.537 indicates that only 53.7% of the variation in GRDP per capita changes can be explained by these two variables, while the remainder is influenced by other factors outside the model. This study recommends strengthening tourism development strategies through improving destination quality, digital promotion, strengthening the local business ecosystem, and increasing competitive accommodation capacity so that the tourism sector can make a more significant economic contribution in the future.